Iterative Methods for Finding Common Solution of Generalized Equilibrium Problems and Variational Inequality Problems and Fixed Point Problems of a Finite Family of Nonexpansive Mappings - Atid Kangtunyakarn (My University, 2010)
Abstract We introduce a new method for a system of generalized equilibrium problems, system of variational inequality problems, and fixed point problems by using "Equation missing"<!-- image only, no MathML or LaTex -->-mapping generated by a finite family of nonexpansive mappings and real numbers. Then, we prove a strong convergence theorem of the proposed iteration under some control condition. By using our main result, we obtain strong convergence theorem for finding a common element of the set of solution of a system of generalized equilibrium problems, system of variational inequality problems, and the set of common fixed points of a finite family of strictly pseudocontractive mappings.
Keywords: Optimization and Variational Analysis